2015
DOI: 10.1101/gr.191452.115
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determinants of improved CRISPR sgRNA design

Abstract: The CRISPR/Cas9 system has revolutionized mammalian somatic cell genetics. Genome-wide functional screens using CRISPR/Cas9-mediated knockout or dCas9 fusion-mediated inhibition/activation (CRISPRi/a) are powerful techniques for discovering phenotype-associated gene function. We systematically assessed the DNA sequence features that contribute to single guide RNA (sgRNA) efficiency in CRISPR-based screens. Leveraging the information from multiple designs, we derived a new sequence model for predicting sgRNA ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
621
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 583 publications
(646 citation statements)
references
References 30 publications
21
621
1
3
Order By: Relevance
“…In Vitro Synthesis of sgRNAs-Candidate sgRNA designs were selected from a number of algorithms, including the sequence scan for CRISPR (40), the Gene Perturbation Platform (41), Chop-Chop (42), and CRISPR Design (43). For most experiments, we selected three to four candidate sgRNAs based on the predicted scores from multiple sgRNA design algorithms and the proximity to desired target sites.…”
Section: Methodsmentioning
confidence: 99%
“…In Vitro Synthesis of sgRNAs-Candidate sgRNA designs were selected from a number of algorithms, including the sequence scan for CRISPR (40), the Gene Perturbation Platform (41), Chop-Chop (42), and CRISPR Design (43). For most experiments, we selected three to four candidate sgRNAs based on the predicted scores from multiple sgRNA design algorithms and the proximity to desired target sites.…”
Section: Methodsmentioning
confidence: 99%
“…Localization of dCas9 using chromatin immunoprecipitation followed by sequencing (ChIP-seq) has indicated that Cas9 stably binds sequences even with multiple mismatches at PAM-distal bases (9,10,14); however, analysis of CRISPRi/a screens has suggested that nearly all mismatches across the length of the target contributed to binding specificity (15). Neither of these approaches gauges occupancy over time, which makes direct measurement of biophysical parameters governing dCas9's interactions with target sequences impossible.…”
mentioning
confidence: 99%
“…The presence of a PAM is basically the principal requirement for the design of a sgRNA. Publically available on-line interfaces have been developed to identify in a given sequence all the potential target sites located near PAMs on both strands of the genomic DNA [36,37]. For the knock-out of a gene, it is recommended to choose a cleavage site in an exon, close to the start codon (or downstream of the last ATG codon in frame to make sure no functional mRNAs will be produced) and with a high probability of leading to a frameshift (out-of-frame score).…”
Section: Selection Of Target Sitesmentioning
confidence: 99%